2014
DOI: 10.1111/cen.12671
|View full text |Cite
|
Sign up to set email alerts
|

Serum Immunoglobulin G4 levels are elevated in patients with Graves’ ophthalmopathy

Abstract: IgG4 levels are evidently increased in patients with GD, and there is a possible relationship between IgG4 and GO. Our results suggest that IgG4 may be helpful in screening GD patients with high risk for GO and may well become a good indicator for the selection of right medication in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 35 publications
2
21
1
3
Order By: Relevance
“…The association with GO is also a matter of interest. Bozkirly et al first suggested that an elevation of IgG4 would preferably be observed in patients with GO (35). In their series the proportion of patients with an IgG4 serum level >135 mg/mL was significantly higher in patients with GO as opposed with that found in patients without GO (37.5 vs 9.1%, respectively).…”
Section: Graves' Diseasementioning
confidence: 88%
See 1 more Smart Citation
“…The association with GO is also a matter of interest. Bozkirly et al first suggested that an elevation of IgG4 would preferably be observed in patients with GO (35). In their series the proportion of patients with an IgG4 serum level >135 mg/mL was significantly higher in patients with GO as opposed with that found in patients without GO (37.5 vs 9.1%, respectively).…”
Section: Graves' Diseasementioning
confidence: 88%
“…Indeed, the prevalence of GD with elevated IgG4 in previously reported series ranges from 6.0 to 11.1%. The highest prevalence (23%) was reported by a single study on a GD series characterized by an extremely high (50%) prevalence of Graves' orbitopathy (GO) (35).…”
Section: Graves' Diseasementioning
confidence: 98%
“…These patients were older and had more hypoechoic areas on ultrasonography, but any histological differences have not been evaluated [41]. An association of Graves ophthalmopathy with elevated serum IgG4 levels has also been found [42], but more data are required to link this to IgG4-RTD.…”
Section: Graves Disease In the Context Of Igg4-rtdmentioning
confidence: 99%
“…It is believed to occur equally among males and females [1,2]. Recent reports have also suggested that a small fraction of Graves' disease patients also have elevated IgG4 levels with some features suggestive of IgG4TD [21,22]. Takeshima K et al reported that 6.4% of 109 patients with Graves' disease had elevated IgG4 titres [21].…”
Section: Igg4 Related Thyroid Disease (Igg4rtd)mentioning
confidence: 99%
“…in patients of Graves' disease with Graves' orbitopathy (GO) as compared to those without orbitopathy, and the levels correlated with clinical activity score [22]. Riedel's thyroiditis, first reported in 1896, is an inflammatory sclerosing disorder of the thyroid, having an estimated incidence of 1.06 cases per 100,000 population [23].…”
Section: Prace Poglądowementioning
confidence: 99%